Spreading the Innovations on the Basis of Leasing - Bivainis, Juozas; Staškevičius, Aurimas Tomas (Ekonomika, 2001)
Leasing at financial rent is an operation when one subject engaged in economic activities (provider of a leasing object) is commited by the contract to acquire from the third person a legal right for the property specified by another subject (recipient of a leasing Object) with the aim to transfer it to the recipient to own and use it in his/her business for the specified rent under the condition that the property (a leasing object) will be purchased by a recipient when he/she repays its cost fixed in a leasing contract. Commonly, leasing operation involves three parties: a recipient, a provider of a leasing Object and a seller. In addition, some other subjects, e.g. financial and ensurance companies. etc. may be involved but their participation is closely connected with the main three parties mentioned above.Modern technologies substituting the obsolescent techniques are always based on innovations. It should be noted that now the clients of leasing companies often choose the objects for leasing rather subjectively not having analyzed them from various perspectives but basing themselves on doubtful information.Modern economics and management have at their disposal a number of various tests as well as evaluation and diagnostic methods for assessing the economic activities. Recently, benchmarking approach has been widely used in different areas.To realize the suggested model of utilizing the innovations based on leasing principle the contract involving three parties, e.g. leasing companies, their clients and innovation foundations, might be most effective. Based on the above contracts, leasing companies, maintaining the links with potential clients could find and store the relevant data as well as assessing the alternative leasing objects from various perspectives. In addition, such contracts may be considered as the basis for obtaining the financial aid from the innovations funds.A set of economic, informational and methodological devices have been developed to ensure more wider utilization of innovations based on leasing practice in the economy of the country. The main principles of data base formation and application as well as the financing of the model realization have been determined. Methods and techniques for qualitative evaluation of the innovative character of the potential leasing objects (contracts) have been established based on benchmarking approach.A model of the integrated coefficients to assess the innovative character of the potential leasing objects. which is One of the major problems in realizing the suggested approach to spreading the innovations, has been proposed. An euristic algorithm based on bench marking principle has been developed for determining the relative values of the innovative character of leasing objects (contracts). Most problematic steps and application procedures of the algorithm have also been discussed.